Uso de Data Warehouse na gestão estratégica da informação: estudo aplicado a uma empresa de tecnologia móbile - Lucas Herbert de Resende Silva (2015)
Contemporary organizations live with the constant competition caused by globalization. Information management is a response of contemporary organizations the competitive environment, which requires agility, innovation and ability to learn. The use of the data warehouse environment and data analysis tools present huge growth because they are used for storage, management and dissemination of information. This research aims to describe, from a case study, the development of the Data Warehouse project applied in a mobile technology company, with operations in the South American market. This organization seeks to improve the analytical tools of the information from the data warehouse environment by storing relevant data to extract patterns of behavior and their customer trends in the use of their services and products. The study, in addition to presenting the Data Warehouse developed environment, demonstrates how users can extract information useful, relevant and economically important. This information is obtained from multiple and voluminous data sources that provide greater competitiveness of the company in the market, as it makes possible the monitoring of products and services of the organization, as well as predict the directions / trends through the data produced.